Danziyev , Ramal - (:unkn) unknown (My University, 2026)
Ramal Mirzahasan oglu Danziyev graduated from the Azerbaijan University of Architecture and Construction (AzUAC) with a Bachelor’s degree in City Cadastre in 2008 and a Master’s degree with honors in the same specialization in 2010. He began his academic career in 2009 as a Laboratory Assistant at the Department of Engineering Geodesy, now the Department of Geomatics, at AzUAC. In 2010, he was promoted to Head of the Laboratory and Assistant. Since 2016, he has been working as a Senior Lecturer at the Department of Geomatics. R.M. Danziyev is the author of more than 50 scientific articles and conference theses, 3 methodological guidelines, and several course programmes. His current research focuses on flood assessment using satellite geodesy and remote sensing technologies.